A Neurological Appearance of Celiac Disease: Is There Any Associated Factor?. Issue 6 (June 2021) - Cavusoglu, Dilek; Olgac Dundar, Nihal; Oztekin, Ozgur; Arican, Pinar; Gencpinar, Pinar; Baran, Masallah
Abstract : Objective: Celiac disease may present with one or more neurological signs and/or symptoms. We aimed to define the incidence of accompanying neurological manifestations in children diagnosed as having celiac disease. Methods: The prospective study included 146 children diagnosed as having celiac disease. The medical records (presentation symptoms, clinical findings, serological test, duodenal biopsy results, lack/deficiency of vitamin, tissue type, accompanying autoimmune disorders) and demographic data of all patients were also reviewed. Results: Thirty-five (23.9%) of the 146 celiac patients exhibited one or more neurological findings. Headache (11.6%) and dizziness (6.1%) were the most common symptoms among neurological manifestations. There was a significant difference between the patients with and without neurological manifestations in terms of sex, biopsy result, and tissue type ( P < 0.05). Moreover, there was a statistically significant difference between tissue types of the patients with and without headache ( P < 0.05). We found that grade 3a by Marsh classification was the most common type among the patients with and without neurological findings in celiac disease. On neuroimaging evaluation of patients, 1 patient with chronic focal ischemic lesion, 1 patient with Chiari type 1 malformation, and 1 patient with subcortical white matter changes were identified. Conclusions: Pathophysiology of neurological involvement in celiac disease is liable for various neurological findings. This study contributes to data suggesting that female sex, mild histopathological form, and human leukocyte antigen DQ2 heterozygosity are related to neurological manifestations, and also human leukocyte antigen DQ2 heterozygosity is associated with headache in celiac disease.